Analisis Efektivitas Pemanfaatan Aplikasi Sistem Rekapitulasi Dalam Proses Pelaksanaan Pemilihan Umum Serentak Tahun 2024 di Kelurahan Hegarsari Kecamatan Pataruman Kota Banjar - Fitri Adila Novianti; Arie Budiawan; Neti Sunarti (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
Based on the research background, it analyzes the effectiveness of utilizing the Recapitulation System application in the simultaneous 2024 general election process in Hegarsari Village, Pataruman District, Banjar City (Case study on the Presidential & Vice Presidential and Legislative elections). This research method uses descriptive qualitative with data collection techniques through interviews, observations, and documentation. The research results show that the effectiveness of utilizing the Recapitulation System application in the simultaneous 2024 general election process in Hegarsari Village, Pataruman District, Banjar City is not yet optimal, as it is hindered by network system issues, the inability of the recapitulation application to fully read the numerical text on Form C due to inaccurate scanning, and many KPPS members still lacking the ability to operate the recapitulation application. This research contributes to expanding the understanding of the practical benefits of the effectiveness of using the Sirekap application in the simultaneous general election process in 2024.